Elan - California State College at Hayward::::::; California State University, Hayward::::::; California State University, East Bay:::::: (1968)
1968 Elan yearbook contains individual and group portraits of faculty, administrators, and students. Photographs of the Dave Brubeck Quartet, The Association, Country Joe and the Fish, Bobby Seale, and Dick Gregory, who performed or spoke on campus during that academic year, are also included.